Neuroprotective Effect of Membrane-Free Stem Cell Extract against Amyloid Beta 25–35-Induced Neurotoxicity in SH-SY5Y Cells - Hye Sook Park; Qi Qi Pang; Young Sil Kim; Ji Hyun Kim; Eun Ju Cho (Applied Sciences, 2021)
Amyloid beta (Aβ) produced by the amyloidogenic pathway induces neurotoxicity, and its accumulation is a well-known cause of Alzheimer’s disease (AD). In this study, the protective effect of membrane-free stem cell extract (MFSCE) derived from adipose tissue against Aβ25–35-induced neurotoxicity in the neuronal cells was investigated. Treatment with MFSCE increased cell viability and decreased lactate dehydrogenase (LDH) release in a dose-dependent manner, compared with the Aβ25–35-induced group. The level of reactive oxygen species (ROS) was significantly increased in neuronal cells induced by Aβ25–35, whereas MFSCE treatment dose-dependently reduced ROS production. Treatment with MFSCE attenuated neuroinflammation and neuronal apoptosis by downregulating inducible nitric oxide synthase, cyclooxygenase-2, and B-cell lymphoma 2-associated X protein in treated SH-SY5Y cells induced by Aβ25–35. Furthermore, MFSCE significantly downregulated the expression of the amyloidogenic pathway-related proteins, such as amyloid precursor protein, β-secretase, preselin-1, and preselin-2. Therefore, this study indicated a neuroprotective effect of MFSCE against neurotoxicity induced by Aβ25–35, suggesting that it is a useful strategy for the treatment of AD.